WASTE PHENOMENOLOGY IN NIGERIA’S POSTMODERN ART - T. E., Akinde; Abokede, O. O.; Akinyemi, A.; Akintonde, M. A. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Globally, the paradigm shift from modern to postmodern art is actively traceable to the 1970s. This shift is known as postmodernism, a movement that embraces limitless enquiry in art, exemplified in “mass culture”; that is synthesis from any and every materials including waste. In Nigeria, this shift emerges in 2000, which became active and clearer in 2003 with Uche Onyishi’s “Ants” masterfully rendered from calabash, cup and wire wastes. Today the surge of wastes appearance in art is phenomenal, instance in plastic, rubber, paper, wires, metal, fabric, glass, woods and etcetera. Practical and technical as the efforts of these artists were at waste to art, it is sad to note that their contributions have not been given commensurate and adequate scholastic attention and publicity. It is on this premise that the study attempts analytical examination of works by selected Nigerian artists. Shortlisted are eight (8) works, Wealth of Nation: Ogoni Nine, Okirika Bale, On the Waterfront, Environment and Object, Root Desecrated, Let’s Turn Time on the Table and Scrap of Evidence, executed between 2007 and 2020. Finding attest pieces phenomenal wastes acculturation, a postmodernist willingness in embracing “mass culture” as against modernist “high art”[1] in Nigerian art. It further reveals artists none proclamation or affirmation of postmodernism, largely for lack of theory and philosophy. The study therefore confers postmodernist or postmodernism on these art practitioners. Conclusively, its findings is hoped to further provoke documentations on waste, art and practice phenomenology from postmodernist standpoint in Nigeria and Africa at large.